Collective self-trapping of atoms in a cavity. (19th August 2021) - Dombi, A; Clark, T W; Williams, F I B; Jessen, F; Fortágh, J; Nagy, D; Vukics, A; Domokos, P
Abstract: We study experimentally the optical dipole trapping of a cloud of cold atoms in a high-finesse cavity in the parameter regime where the atomic back-action on the cavity mode is significant. Back-action based effects lead to state selective optical manipulation schemes. We identify a parameter range where the collective back action of the atoms is needed for the trapping, i.e. a single atom would not be trapped under the same laser drive conditions. The collective self-trapping is demonstrated by the observation of a significant increase of the trapping time as a function of the atom number. The atomic back action on the cavity field gives rise to a simultaneous real-time monitoring of the number of trapped atoms. This is used to show a non-exponential collapse of the atom trap.